Interconnected crises and design complexity - Losasso, Mario (TECHNE - Journal of Technology for Architecture and Environment, 2022)
Crisis and new generations, along with environment and technology, are the key words of a debate which, since the 1970s, has tackled the theme of the periodic crises that cross our contemporary world: in the present, the crisis is now expressed in multiple intertwined crises since the limits between environmental, social and health crises are blurred and impose the need for a response with similar degrees of complexity and multipolarity (Scomodo, 2021, p.350). The accumulation of transnational and local critical points has led to a saturation of the globalised planetary system, while the phase of uncertainty defines trends towards de-standardisation, increasing heterogeneity, social instability and growing inequalities (Mingione, 2019, p.11). The ideology of globalisation has undergone a deep redefinition with increasing gaps due to uncontrolled economic liberalism and the emergence of movements that bring extreme radicalisation to society (Piketty, 2020, p. 1167).